Factors Affecting Mental Well-Being of Remote Working Females in the Indian IT Sector - Fuladi, Rimzim (Digital Repository of Theses, 2025)
Background The rise of remote and hybrid work in India’s IT sector has reshaped the professional landscape for women. While offering flexibility in form, these models often reinforce deeper structural pressures—eroding work–life boundaries, amplifying caregiving burdens, and leaving gender-specific health needs invisible. This study explores how these complex and intersecting factors impact women’s mental well-being and what organisational mechanisms can be implemented to create more inclusive and supportive work environments. Methods A layered, explanatory approach was employed to capture both individual experiences and organisational patterns. Insights were derived from women's reflections and organisational realities, presenting a cohesive understanding of the remote work ecosystem and its gendered effects. Results Remote work is frequently perceived as liberating, but it often blurs personal and professional boundaries, leading to emotional fatigue and loss of recovery time. Caregiving responsibilities, particularly for children and elderly family members, are intensified without structured institutional support. Menstruation and menopause-related challenges remain largely unaddressed, resulting in discomfort, disengagement, and silence. A lack of empathetic communication, informal interaction, and recognition further isolates women, diminishing their sense of belonging and visibility in virtual settings. However, where organisations demonstrate sensitivity to life-stage needs, offer flexibility grounded in empathy, and maintain clear, inclusive communication, women report stronger psychological safety and greater job satisfaction. When leadership is emotionally intelligent and policies are intentionally inclusive, the mental well-being of women improves meaningfully, enabling greater engagement, retention, and performance. Discussion and Conclusion The findings challenge the assumption that flexibility alone ensures equity. Mental well-being is not a by-product of remote access, but a reflection of how work is structured, led, and culturally supported. Sustainable support requires acknowledging the full range of gendered experiences, across caregiving, reproductive health, and virtual visibility, and incorporating this understanding into policy, leadership development, and daily practice. This research provides a strategic blueprint for the IT sector: codifying reproductive and caregiving policies, empowering managers through inclusive training, ensuring visibility for remote contributors, and fostering cultures of psychological safety. These changes not only support the mental health of women but also position organisations as adaptive, equitable, and future-ready employers.